2018
DOI: 10.1108/jhr-05-2018-033
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an educational program on knowledge, attitudes and intentions regarding condom and emergency contraceptive pill use among Thai female university students

Abstract: Purpose University students who have low knowledge, attitudes and intentions regarding the prevention of unintended pregnancies may experience higher rates of unintended pregnancies. An educational program was developed based on the self-efficacy theory and peer-led education to improve unintended pregnancy problems among university students. The purpose of this paper is to examine the effect of an educational program on knowledge, attitudes and intentions regarding the use of condoms and emergency contracepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
4
14
0
1
Order By: Relevance
“…Although limited in time, this study did show that participating students had positive attitude and awareness toward sexuality as did happen in other research [5,23,25,[29][30][31]. Because more Thai adolescents are becoming sexually active earlier, sex education classes like the one piloted should next target 10-year-old students.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Although limited in time, this study did show that participating students had positive attitude and awareness toward sexuality as did happen in other research [5,23,25,[29][30][31]. Because more Thai adolescents are becoming sexually active earlier, sex education classes like the one piloted should next target 10-year-old students.…”
Section: Discussionmentioning
confidence: 48%
“…In Thailand, many organizations have tried to increase sex education, but most of these are extra programs or out-of-school curriculum that require many more hours than is normally allocated to the subject [5,11,19,24,25,[28][29][30]. Some of these programs also have the luxury of bringing in experts.…”
Section: Discussionmentioning
confidence: 99%
“…In research from Korea, 88.2% of students were aware of EC, while 35% were able to answer the question of usage periods of oral contraceptives; in contrast, 23.1% of university students in South India were reported to have heard of EC [31]. Research conducted with female students in Ethiopia reported that the knowledge score of 49.8% of students was "moderate" [32]. Among young people aged 13-25 in San Francisco, women had a higher rate of EC familiarity than men (86% vs. 70%), while 44% reported the time of use incorrectly [33].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that 97.2% of the nursing students accessed information at school, while only 7.1% of the students in the social services department accessed it at school [13]. Some research suggests that education given to students had positive effects on EC knowledge, attitude and intentions [32]. Gölbaşı et al (2012) [17] reported the sources as magazines (61.2%), friends (46.1%) school (39%), and Internet/TV (66.2%); Arslan (2014) reported the primary source of knowledge for reproductive health as the Internet [17,24].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference is respondents from field of Health Sciences had some knowledge of reproductive health rights from their classes and trainings. Having knowledge on reproductive health prevents premarital sexual intercourse and unintended pregnancy [10,21,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%